Hospital admission rates for meningitis and septicaemia caused by Haemophilus influenzae, Neisseria meningitidis, and Streptococcus pneumoniae in children in England over five decades: A population-based observational study - Martin, N; Sadarangani, M; Pollard, A; Goldacre, M (Lancet, 2014)
Background: Infection with Haemophilus influenzae, Neisseria meningitidis, and Streptococcus pneumoniae causes substantial mortality and long-term morbidity in children. We know of no study to assess the long-term trends in hospital admission rates for meningitis and septicaemia caused by these pathogens in children in England. We aimed to do such a study using routinely reported data in England. Methods: In this population-based observational study, we used datasets that include routinely collected administrative statistics for hospital care: the Hospital In-Patient Enquiry (data for England from 1968 to 1985), the Hospital Episode Statistics dataset (data for England from 1989 onwards), and the Oxford record linkage study (data for Oxfordshire and surrounding areas from 1963 to 2011). We analysed annual age-specific and age-standardised admission rates in children younger than 15 years with H influenzae, meningococcal and pneumococcal meningitis, and septicaemia. Findings: We saw a reduction in hospital admission rates for childhood invasive bacterial disease after the introduction of conjugate vaccines against H influenzae, N meningitidis, and S pneumoniae in England. Annual incidence of H influenzae meningitis per 100 000 children decreased from 6·72 admissions (95% CI 6·18-7·26) in 1992 to 0·39 admissions (0·26-0·52) in 1994, after the introduction of routine H influenzae type b vaccination. We saw a small rise in admissions in the early 2000s, peaking at 1·24 admissions per 100 000 children (0·99-1·48) in 2003, which decreased to 0·28 per 100 000 children (0·17-0·39) by 2008 after the introduction of catch-up (2003) and routine (2006) booster programmes for young children. Meningococcal disease increased during the 1990s, reaching a peak in 1999, with 34·54 admissions (33·30-35·78) per 100 000 children. Hospital admissions decreased after the meningococcal serogroup C vaccine was introduced in 1999 and was 12·40 admissions (11·68-13·12) per 100 000 in 2011. Admissions for invasive pneumococcal disease increased from the 1990s reaching a peak in 2006 at 4·45 admissions for meningitis (95% CI 4·0-4·9) per 100 000 children and 2·81 admissions for septicaemia (2·45-3·17) per 100 000 children. A reduction in admissions occurred after the introduction of the pneumococcal conjugate vaccine in 2006: hospital admission rates in 2011 were 2·03 per 100 000 children for meningitis and 1·12 per 100 000 children for septicaemia. Interpretation: Vaccine-preventable invasive bacterial disease in children has decreased substantially in England in the past five decades, most notably with the advent of effective conjugate vaccines since the 1990s. Ongoing disease surveillance and continued development and implementation of vaccines against additional pneumococcal serotypes and serogroup B meningococcal disease are important. Funding: None. © 2014 Elsevier Ltd.